Pelatihan Digital Marketing untuk Meningkatkan Penjualan Batik Pamekasan di Desa Sentra Batik Klampar Kecamatan Proppo Kabupaten Pamekasan - Reza Mubarak; Subairi Subairi; Umarul Faruq; Ihlasul Fatoni; Fithratul Lailiyah (JPM: Jurnal Pengabdian Masyarakat, 2023)
Pamekasan is the largest batik-producing district in Madura. There are around 28 batik centers spread across several sub-districts, and the most are in the Proppo sub-district, namely 12 batik centers. One of these batik centers is Klampar Village. Product penetration into the market has also been quite slow because the availability of information about Pamekasan batik has not been widely exposed. Therefore, it is necessary to increase promotion and sales using digital marketing. The focus of this digital marketing training activity is education about the potential of the digital market and the importance of digital marketing, followed by training on marketing batik products through social media. This type of research is descriptive qualitative research. The result of this activity is that participants are trained to utilize social media to optimize marketing via the internet. Participants are guided by a resource person. And at the end of the activity, an evaluation is carried out to see how big the impact is on digital marketing through social media.